Microvesicles Derived From Human Mesenchymal Stem Cells Restore Alveolar Fluid Clearance in Human Lungs Rejected for Transplantation. Issue 9 (6th April 2015) - Gennai, S.; Monsel, A.; Hao, Q.; Park, J.; Matthay, M. A.; Lee, J. W.
<x xml:space="preserve">Abstract</x> The need to increase the donor pool for lung transplantation is a major public health issue. We previously found that administration of mesenchymal stem cells "rehabilitated" marginal donor lungs rejected for transplantation using ex vivo lung perfusion. However, the use of stem cells has some inherent limitation such as the potential for tumor formation. In the current study, we hypothesized that microvesicles, small anuclear membrane fragments constitutively released from mesenchymal stem cells, may be a good alternative to using stem cells. Using our well established ex vivo lung perfusion model, microvesicles derived from human mesenchymal stem cells increased alveolar fluid clearance (i.e. ability to absorb pulmonary edema fluid) in a dose‐dependent manner, decreased lung weight gain following perfusion and ventilation, and improved airway and hemodynamic parameters compared to perfusion alone. Microvesicles derived from normal human lung fibroblasts as a control had no effect. Co‐administration of microvesicles with anti‐CD44 antibody attenuated these effects, suggesting a key role of the CD44 receptor in the internalization of the microvesicles into the injured host cell and its effect. In summary, microvesicles derived from human mesenchymal stem cells were as effective as the parent mesenchymal stem cells in rehabilitating marginal donor human lungs.